Surveillance of antibiotic use in the private sector in Namibia using sales and claims data - Dawn Dineo Pereko; Martie S Lubbe; Sabiha Y Essack (Journal of Infection in Developing Countries)
Introduction: Antibiotics are among the most commonly used therapeutic agents for humans globally, and their use has been associated with the development of resistance. The objective of this study was to identify sources for quantifying antibiotic usage patterns and to assess such use in ambulatory patients in the private health sector of Namibia. Methodology: A retrospective analysis of prescription claims data and sales data for the period 2008 to 2011 was conducted. Antibiotic use was expressed in the number of antibiotic-containing prescriptions and volume of units sold and then standardized using defined daily dose per 1,000 inhabitants per day. Results: Antibiotic usage was highest in females (53%), in people 18–45 years of age (41%), and in Windhoek (34%). Overall, wholesale data showed higher antibiotic use than prescription claims data. However, both sources showed similar patterns of antibiotic use. Penicillins were the most used pharmacological group, with amoxicillin/clavulanic acid combination being the most used of the agents. Conclusion: Antibiotic use in the private sector of Namibia is comparable to that of high-consuming European countries such as Italy. A trend observed in this study was the decrease in the use of narrow-spectrum antibiotics in favour of broad-spectrum and newer antibiotics. Since this was the first study to assess antibiotic use in the private sector of Namibia, it could serve as a starting point for continued monitoring of antibiotic use in the whole of Namibia in the context of the World Health Organization’s Global Action Plan to contain antibiotic resistance.